POLITIK HUKUM DALAM PERUMUSAN KALENDER ISLAM (Studi Tentang Kebijakan Kalender Nabi Muhammad SAW di Jazirah Arab dan Kalender Sultan Agung di Tanah Jawa) - Musonnif, Ahmad (IAIN Tulungagung, 2016)
Calendar constitutes an important element of a rulerâs policy to controlthe people and to lead to the achievement of the rulerâs politicalagenda. The Prophet Mohamed, as a ruler of society, also utilizesthe calendar to achieve his main mission to make the society worshipto one God (Tauhid). In the case of Javanese Ruler, Sultan Agung,he utilizes the Javanese calendar to maintain the Islamic-Javanesesyncretism teaching.Kata kunci: Politik Hukum, Kalender Islam, Kalender Sultan Agung